Mathematical modeling of the environmental radioactive pollution during oil and gas wells drilling - Burla, Oksana; Ablieieva, Iryna; Plyatsuk, Leonid; Malovanyy, Myroslav (Lviv Politechnic Publishing House, 2017)
The aim of paper was development of an adequate mathematical model for predicting the level of environmental pollution by radionuclides emitted as a result of oil wells drilling. This problem was solved using Gaussian Plume Model which allowed to determine the concentration of radionuclides at a given point in space. Impurity flux density in Bq/(m2 s) was been simulated.
Keywords: Gaussian model; radioactive dispersion; air pollution; radionuclides distribution; wells drilling